STUDY ON THE DEVELOPMENT OF ETHNIC SONG AND DANCE COSTUME DESIGN IN GUANGXI, CHINA - Chen, Tian; Mayusoh, Chanoknart; Inkuer, Akapong; Puntien, Pisit (วารสารศิลปกรรมและการออกแบบแห่งเอเชีย, 2024)
China, a nation celebrated for its cultural diversity, presents a rich mosaic of dance traditions thriving among its diverse ethnic communities. Within this cultural tapestry, the discipline of costume design for ethnic musical theaters assumes a pivotal role, shaping the essence of stage artistry. Despite its profound importance, a conspicuous void exists in theoretical research within this domain. This study embarked on a multifaceted exploration with three core objectives including: 1) Exploring Evolution and Socio-Cultural Dynamics: The study endeavored to unravel the correlation between the evolving landscape of stage costume design for ethnic minorities in Guangxi and the concurrent socio-cultural developments spanning from 1949 to 2020. 2) In-Depth Analysis of Design Methods and Procedures: It aimed to provide a comprehensive analysis, shedding light on the intricate methods and procedures that underlie the art of stage costume design for ethnic minorities in Guangxi. 3) Creation of Distinctive and Contemporary Stage Attire: The research extended its reach by crafting distinctive and contemporary stage costumes tailor-made for the opera "The Great Han Sea Road," the dance "Feather People," and the song and dance performance "Night in Guilin". The study employed a qualitative approach, analyzing interview content using descriptive statistics and stratified multiple regression analysis. Data was meticulously gathered and structured, drawing from insights from 8 performance groups, 20 practitioner surveys, and 8 interviews. An additional 30 audience surveys contributed to validating the research findings, affirming their consistency and significance. The design methodology initially evolved focusing on enhancing traditional attire, introducing innovations in color and style, and ultimately striving to harmonize visual aesthetics with tradition. The study revealed a discernible pattern in the development of ethnic minority stage costumes in Guangxi during the period from 1949 to 2020, characterized by a cyclic journey of traditional innovation and return to tradition (e.g., elements of style, color, and fabric), mirroring broader societal transformations in China. This research provided a multifaceted exploration into the intricate world of ethnic minority stage costume design in Guangxi, elucidating its evolution, cultural resonance, and practical applications within the performing arts. The findings have fostered innovative practices within the realm of stage costume design, manifesting prominently in the opera "The Great Han Sea Road," the dance "Feather People," and the song and dance spectacle "Night in Guilin"